2016
DOI: 10.18174/400306
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and habitat preference of harbour seals (Phoca vitulina) in the Dutch North Sea

Abstract: The Management of Wageningen Marine Research is not responsible for resulting damage, as well as for damage resulting from the application of results or research obtained by Wageningen Marine Research, its clients or any claims related to the application of information found within its research. This report has been made on the request of the client and is wholly the client's property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
0
14
1
6
Order By: Relevance
“…This also seems to be reflected in the movement of seals that tend to forage further offshore during the winter (Aarts et al. ). In addition, also other sources of mortality (e.g., predation by cormorants or by‐catch in the shrimp fishery [Leopold et al.…”
Section: Discussionmentioning
confidence: 99%
“…This also seems to be reflected in the movement of seals that tend to forage further offshore during the winter (Aarts et al. ). In addition, also other sources of mortality (e.g., predation by cormorants or by‐catch in the shrimp fishery [Leopold et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent tagging and genetic studies indicate that especially juvenile harbour seals undertake movements across much greater distances than previously reported, and thus potentially could have played a larger role in transporting PDV longer distances. For instance, Wadden Sea harbour seals have been shown to undertake foraging trips of a couple of hundred kilometres into the North Sea (Dietz et al, 2013;Tougaard et al, 2008;Aarts et al, 2016), and recent population genetic analyses suggested movements among the seals in southern England, France and the Dutch Wadden Sea (Olsen et al, 2017). Likewise, tagging of harbour seals in the fall and early winter of 2016 provided the first documented movements from a haul-out in southern Kattegat to the central Limfjord (Rune Dietz and collaborators, unpublished) by an animal that has now been genetically determined to originate from the Limfjord (Morten Tange Olsen, unpublished).…”
Section: Spread Of Pdv In 2002 Through Multiple Transmission Eventsmentioning
confidence: 99%
“…It has been hypothesized that the unusual mass migration of harp seals in the winter and spring 1987/1988 lead to the introduction of the virus to the European harbour seals in 1988 (Haug & Nilssen, 1995;Nilssen et al, 1998), but the exact timing of these events have never been investigated, and a vector for the 2002 epidemic has not been proposed. Moreover, while the long-distance transmission events of PDV among harbour seal colonies was initially suggested to be aided by the less susceptible and more mobile grey seal (Haliocherus grypus) (Härkönen et al, 2006;McConnell et al, 1999) more recent tagging data indicate that while harbour seals are, in general, philopatric, individual seals occasionally undertake long-distance movements (Dietz et al, 2013;Reijnders et al, 2010;Tougaard et al 2008;Aarts et al, 2016). Therefore, dispersing harbour seals could have served as a vector for spreading the virus across Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising improvement of these models, as recommended by the authors, would be a better representation of the effects of sediment and wind. Aarts et al (2016) show that harbour seal distribution in the Dutch North Sea is concentrated near the haul-out sites in the Wadden Sea and Southern Delta areas, with areas further offshore visited less frequently. This is partly a 'concentration effect' because all seals that use haul-out sites are concentrated in relatively small areas, and the paths between these and the foraging areas therefore have an extremely high abundance.…”
Section: Implications For Monitoring and Evaluation Programmementioning
confidence: 92%